(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
The oral cavity and gastrointestinal tract form a unified anatomical and functional system where disturbances in one part inevitably influence the other. The study explores the bidirectional relationship between oral health and gastrointestinal disorders, emphasizing their shared microbiome, inflammatory pathways, and systemic consequences. It highlights how oral diseases such as periodontitis and caries can exacerbate gastrointestinal pathologies, including gastritis, peptic ulcer disease, inflammatory bowel disorders, and even liver dysfunction. Similarly, gastrointestinal imbalances, particularly those involving the gut microbiota, can contribute to oral dysbiosis, mucosal inflammation, and halitosis. This work presents preventive and therapeutic strategies to maintain oral-gastrointestinal harmony through microbiome modulation, diet optimization, and integrated medical-dental approaches. The research underscores the importance of interprofessional collaboration and patient education in preventing the progression of oral and gastrointestinal diseases. The interdependence between the oral cavity and the gastrointestinal tract represents one of the most significant aspects of human systemic health. Both anatomical regions are interconnected through functional, microbial, and immunological mechanisms that establish a two-way influence. Disorders originating in the oral cavity, such as gingivitis, periodontitis, or dental caries, can lead to systemic inflammation and affect the gastrointestinal mucosa, predisposing individuals to gastritis, peptic ulcers, or irritable bowel syndrome. Conversely, gastrointestinal disturbances, including dysbiosis, reflux disease, or malabsorption, can alter salivary secretion and oral microflora balance, provoking oral mucosal lesions, halitosis, or enamel erosion. The purpose of this study is to explore the bidirectional relationship between oral and gastrointestinal health, identify pathogenic factors contributing to mutual disease progression, and suggest preventive and therapeutic strategies to restore systemic equilibrium. The research findings emphasize the necessity of integrative medical and dental collaboration to improve diagnostic precision, therapeutic efficacy, and patient outcomes.